Exposure to Perfluoroalkyl Substances During Pregnancy and Fetal BDNF Level: A Prospective Cohort Study - Yu, Guoqi; Luo, Fei; Nian, Min; Li, Shuman; Liu, Bin; Feng, Liping; Zhang, Jun (Frontiers in Endocrinology, 2021)
Background Humans are widely exposed to environmental perfluoroalkyl substances (PFAS), which may affect fetal neurodevelopment. Brain-derived neurotrophic factor (BDNF) is an important factor in neurodevelopment, but its role in PFAS-induced neurotoxicity is unclear. We investigated the association between prenatal PFAS exposure and fetal BDNF level in the umbilical cord blood in a large prospective cohort. Methods A total of 725 pregnant women who participated in the Shanghai Birth Cohort were included. 10 PFAS were measured by high-performance liquid chromatography/tandem mass spectrometry (HPLC/MS-MS) in the plasma samples of early pregnancy. The BDNF level was determined by ELISA. The concentration of total mercury (Hg) in the umbilical cord blood was tested by cold vapor atomic absorption spectrometry (AAS) and included as a main confounder, along with other covariates. Multiple linear regression was used to explore the associations between PFAS concentrations and BDNF level. Quantile-based g-computation was applied to explore the joint and independent effects of PFAS on BDNF level. Results The mean BDNF level in the total population was 10797 (4713) pg/ml. Male fetuses had a higher level than female fetuses (P0.001). A significant positive association was observed between PFHxS and BDNF level after adjusting for potential confounders [β=1285 (95% CI: 453, 2118, P=0.003)]. No association was observed between other PFAS congeners and BDNF level. Results of the mixed exposure model showed that the joint effects of PFAS mixture were not associated with BDNF [β=447 (95% CI: -83, 978, P=0.10)], while the positive association with PFHxS exposure remained significant after controlling for other PFAS [β=592 (95% CI: 226, 958, P=0.002)]. The above associations were more prominent in male [β=773 (95% CI: 25, 1520, P= 0.04)] than female fetuses [β=105 (95% CI: -791, 1002, P= 0.82)] for the mixed effects. Conclusions Prenatal exposure to PFHxS was associated with an increased BDNF level in the umbilical blood, especially in male fetuses.